Perkembangan Pembuatan Tenun Melayu Siak : Suatu Tinjauan Historis - Bunari Bunari; Asyrul Fikri; Piki Setri Pernantah; Yanuar Al-Fiqri (Diakronika, 2021)
The siak weaving is a cultural heritage of Riau Malay. The motifs on the Siak Tenun have certain philosophical meanings. In addition, in the manufacturing process, there has been a development both from the materials and tools used. The study in this paper aims to describe the development of Siak weaving techniques based on the categories of materials and tools used from time to time. The method used in this study is the historical method with heuristic, verification, interpretation, and historiography stages. The result of the study is that the making of Siak Weaving has developed in terms of the materials and tools used. In terms of materials, at the beginning of its development using materials from silk, gold, and silver threads. However, since 1950 the weavers began to use cotton threads along with the high prices of silk, gold, and silver threads. Furthermore, in terms of tools, in 1764 the first weaving tool used was the tumpu loom. The tools used for the manufacture of Siaik weaving are increasingly developing, since 1990 it has been replaced by non-machine weaving tools (ATBM). The development of the Siak Tenun making tool to increase production output and shorten processing time. From the results of the study, it can be concluded that changes in the weaving production equipment affect the impact, including the number of workers, budget efficiency, quality, and quantity of production.